(3GdETGQI Edi Yde GdYHGQIs - (3eMeO Hf CMeO Hf YeQ GdSGdej, CHh YHO Gddg,J (B800 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCQhGM haGdb GdEUHGM deG UGQJ YHGQI GdQDjG s
(3BNQgG (B:s
(3jfJgi CKfGA GdHGH GdJGSY ddQLGd s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(396 d) s
Keywords: (3JYHjQ GdQDjGs